THE INFLUENCE OF PRODUCT QUALITY AND LOCATION ON CONSUMER PURCHASE DECISIONS: A CASE STUDY OF KOPI KILA - Putri, Alya Ayunda; Sukatmajaya, Ahmad (Kinerja, 2025)
This study aims to find out "The Influence of Product Quality and Location on Purchase Decisions on Kopi Kila". The sample in this study amounted to 160 respondents. This study uses validity tests, reliability tests, normality tests, multicollinearity tests, and heteroscedasticity tests. The analysis in this study used multiple regression analysis, multiple correlation analysis, determination coefficients and hypothesis tests. The results of the study in the Product Quality (X1) variable has a positive and significant effect on purchase decision (Y) with a tcount value > t table (19.032 > 1654) and a sig value < a value (0.00 < 0.05 and Location (X2) had a positive and significant effect on the purchase decision (Y) with a tcount value > t table (13.608 > 1.654) and a sig value < α value (0.00 < 0.05). The correlation value is 0.851 which means that it shows a very strong relationship. The value of the determination coefficient given by Product Quality (X1) and Location (X2) to the Purchase Decision (Y) was 72% and the remaining 28% was influenced by other factors that were not analyzed.